2018
DOI: 10.1159/000488005
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of High Levels of Alpha-Melanocyte-Stimulating Hormone in Energy Balance Among Obese Adolescents

Abstract: Background: Deregulation of orexigenic and anorexigenic pathways occurs among adolescents with obesity. Alpha-melanocyte-stimulating hormone (α-MSH) is a key catabolic mediator of energy homeostasis and an important anorexigenic neuropeptide in the control of energy balance and thermogenesis. However, it was not well explored if α-MSH can modulate long-term weight loss therapy responses in a dependent manner according to its concentration. Our hypothesis is that a high α-MSH concentration at baseline promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Meanwhile, there are some reports that α-MSH is involved in energy balance by regulating appetite stimulation based on the relationship with orexigenic neuropeptides and leptin [ 26 , 27 ]. Kravchychyn et al [ 28 ] reported that the long-term α-MSH treatment promoted a significant improvement in body adiposity through the regulation of anorexigenic/orexigenic pathways in obese adolescents. From the above results, α-MSH appears to be an important substance involved in the complex mechanisms of energy balance control.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are some reports that α-MSH is involved in energy balance by regulating appetite stimulation based on the relationship with orexigenic neuropeptides and leptin [ 26 , 27 ]. Kravchychyn et al [ 28 ] reported that the long-term α-MSH treatment promoted a significant improvement in body adiposity through the regulation of anorexigenic/orexigenic pathways in obese adolescents. From the above results, α-MSH appears to be an important substance involved in the complex mechanisms of energy balance control.…”
Section: Discussionmentioning
confidence: 99%
“… • The probiotic bacterium, Hafnia alvei HA4597, has been shown to reduce feed intake by patients, improving weight loss during dieting 283 . This was linked to the expression of ClpB, a protein similar to α-melanocyte stimulating hormone, which is involved in the regulation of energy balance 284 . • FMT has been studied for inducing remission in patients with ulcerative colitis 285 .…”
Section: Methods Of Microbiome-based Interventions Their Rationales A...mentioning
confidence: 99%
“…Analyses of serum glucose, total cholesterol (TC), triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C) levels were conducted by commercially available kits (Pars Azmoon Inc., Tehran, Iran) [ 21 ]. Serum insulin [ 23 ] and plasma concentrations of α-MSH and AgRP were measured by enzyme-linked immunosorbent assay kits (Bioassay Technology Laboratory, Shanghai Korean Biotech, Shanghai City, China) [ 24 ] based on manufacturer’s protocol. Serum low-density lipoprotein cholesterol (LDL), the homeostasis model of assessment ratio (HOMA-R) and quantitative insulin sensitivity check index (QUICKI) were calculated using the protocols which have been described by Friedewald et al [ 25 ], Matthews et al [ 26 ] and Katz et al [ 27 ], respectively.…”
Section: Methodsmentioning
confidence: 99%